Influence of Bulb Size and Spacing on Crop Growth, Yield and Quality of Onion (Allium cepa) Seed under High Altitudes of Leh-Ladakh - NARENDRA SINGH; DORJEY ANGCHOK (Seed Research, 2026)
Three bulb size (2.5 cm, 5.0 cm and 7.5 cm diameter) and three spacing combinations (45 cm x 10 cm, 45 cm x 20 cm and 45 cm x 30 cm), showed significant effects on crop growth, yield and quality attributes (except germination %) of the seeds during seed production of onion cv. Early Grano - 50 at Defence Institute of High Altitude Research, Leh-Ladakh (J&K). The maximum seed yield of 10.4 q/ha was obtained with bulb size of 7.5 cm dia. The closer spacing of 45 cm x 10 cm had marked influence on plant height and seed yield. However, wider spacing of 45 cm x 30 cm recorded better performance or almost all the other studied attributes.